Morphology of Amphora lunulata A.H. Wachnicka & E.E. Gaiser and its transfer to Seminavis D.G. Mann. Issue 1 (2nd January 2022) - Li, Chenhong; Tan, Lanyu; Gao, Yahui; Li, Xuesong; Sun, Lin; Liang, Junrong; Zhang, Jun; Huang, Luqiang; Chen, Changping
Abstract : An amphoroid diatom epiphytic on seagrass leaves from Hainan Province, southern China was identified as Amphora lunulata Wachnicka & Gaiser. It is characterized by a semi-elliptical valve with acute apices, ventral striae interrupted at the centre, and an axial area, which is well developed on the dorsal side but narrower at the centre, in accordance with its original description. However, as seen under the scanning electronic microscope, A. lunulata presents a combination of features that is consistent with the description of the genus Seminavis, i.e., slit-like areolae covered by hymenes, terminal fissures hooked toward the dorsal side and unornamented valvocopula. Therefore, we redefined the taxonomic status of Amphora lunulata A.H. Wachnicka & E.E. Gaiser and transferred it to the genus Seminavis . We compared the morphometric characteristics of Seminavis lunulata to those of the original description from Wachnicka & Gaiser (2007) and other taxa in Seminavis, including Seminavis atlantica M. Garcia, Seminavis eulensteinii (Grunow) D.B. Danielidis, K. Ford & D. Kennett, Seminavis heidenii D.G. Mann in D.B. Danielidis & D.G. Mann.